KEANTIAJAIBAN SUPER TOTAL SELIMUT PADA COMB SISI GRAF TANGGA SEGITIGA DENGAN AMALGAMASI GRAF SIKEL DAN KAITANNYA DENGAN KETERAMPILAN BERPIKIR TINGKAT TINGGI - Azmi, Ulul; Dafik, Dafik; Setiawani, Susi (Department of Mathematics Education , University of Jember, 2015)
Abstract. Cover total Labeling (a, d) -H- anti magical on a graph G = (V, E) is a bijective function of the points and edges on the set of integers from 1, 2, 3, ... |V(G)|+|E(G)|, for every subgraph H of G which is isomorphic to H has a total different labeling and form of arithmetic sequence. H-labeling is said to have super anti magical if point labeling and edge labeling where the label side of a point less than the edge side label labeling side is done after labeling point. One technique that can be applied to get a super anti-magic total labeling blanket on a graph that is engineering the partition of the set of integers with different sets d. Partition symbolized In this article examines the super labeling (a, d) - Cm+2- anti magical total covering of an edge comb product triangular ladder graph and amalgamation cycle graph. Graf obtained by taking one copy of triangular ladder graph and |E(L)| copies of amalgamation cycle graph and grafting the i-th copy of amalgamation cycle graph at the edges to the i-th edge of triangular ladder graphwhich denoted The graph is labeled in order to obtain a new partition variations. Kata Kunci:Super (a,d)-Cm+2-Antimagic Total Selimut, Comb Sisi Graf Tangga Segitiga dengan Amalgamasi Graf Sikel